SOSIALISASI PENCEGAHAN DAN PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) - Syaifullah Syaifullah; Bima Guntara; Dadang Dadang; Rio Hendra; Ferry Agus Sianipar (LPPM Universitas Pamulang, 2021)
Domestic violence is an act of violence against women that is often invisible. Along with cases of domestic violence that are increasing day by day, the government issued a Law on the Elimination of Domestic Violence, with the aim that victims of domestic violence, especially women, are expected to obtain legal protection. The problem that arises then is how to protect the law against victims of Domestic Violence (KDRT) to prevent criminal acts of domestic violence. The existence of Law Number 23 of 2004 concerning the Elimination of Domestic Violence is expected to be able to provide significant legal protection for victims of Domestic Violence (KDRT). The forms of protection regulated in this law are temporary protection from the police, court protection and placement of victims in